Nomogram to predict 3 month prognosis of acute ischemic stroke among young adults - Qian He; Qian He; Miaoran Wang; Haoyue Zhu; Ying Xiao; Rui Wen; Xiaoqing Liu; Yangdi Shi; Linzhi Zhang; Bing Xu (Frontiers in Neurology)
ObjectiveThis study aimed to develop and validate a nomogram for predicting the risk of 3 months adverse outcomes among young adults with acute ischemic stroke (AIS).MethodsPatients aged between 18 and 50 with acute ischemic stroke (AIS) at the Shenyang First’s People Hospital, between January 1st 2017 to May 30th 2023 were included in this retrospective study. The primary outcome was a three-month unfavorable outcome, evaluated with modified Rankin Scale (mRS > 2). Univariate logistic regression was used to select the independent factors of prognosis and multivariate logistic regression to establish a new nomogram model. We used the area under the receiver-operating characteristic curve (ROC) to evaluate the discriminative performance and used the calibration curve with Hosmer-Lemeshow goodness of fit test to assess the calibration performance of the risk prediction model. Decision curve analysis (DCA) was applied to assess the clinical utility of the nomogram.ResultsA total of 1,015 patients were enrolled. Gender (male vs. female; Odds ratio[OR], 0.5562[95% Confidence Interval (CI), 0.3104–1.0478]; p = 0.053), family history of stroke (OR, 3.5698[95%CI 1.5632–8.0329], p < 0.001), prior stroke (OR, 2.1509[95%CI 1.2610–3.6577], p < 0.001), previous heart disease (OR, 3.4047[95%CI, 1.7838–6.6976], p < 0.01) toast type (cardio-embolism stroke vs. large-artery atherosclerosis (LAA), OR, 0.0847[0.0043–0.5284], p < 0.01), toast type (stroke of undetermined etiology vs. LAA, OR, 0.0847[0.0439–0.5284], p < 0.01), mRS at admission (OR, 15.2446 [9.1447–26.3156], p < 0.0001), adherence to medication (OR, 2.1197[95%CI, 1.1924–3.7464], p < 0.001), systolic blood pressure (SBP; OR, 1.0145[1.0041–1.0250], p < 0.001), and lactate dehydrogenase (LDH; OR, 1.0060[1.0010–1.0111], p < 0.01) were related to 3 months adverse outcomes among young adults with AIS. The nomogram displayed excellent calibration and discrimination. DCA confirmed the clinical applicability of the model.ConclusionThe nomogram comprised of gender, family history of stroke, prior stroke, previous heart disease, toast type, mRS score at admission, adherence to medication, SBP and LDH may predict 3 months adverse outcomes among young adults with AIS.